Comprehensive geriatric assessment in older people: an umbrella review of health outcomes. (6th May 2022) - Veronese, Nicola; Custodero, Carlo; Demurtas, Jacopo; Smith, Lee; Barbagallo, Mario; Maggi, Stefania; Cella, Alberto; Vanacore, Nicola; Aprile, Pierangelo Lora; Ferrucci, Luigi; Pilotto, Alberto; ,; et al.
Abstract: Background: Comprehensive geriatric assessment (CGA) has been in use for the last three decades. However, some doubts remain regarding its clinical use. Therefore, we aimed to capture the breadth of outcomes reported and assess the strength of evidence of the use of comprehensive geriatric assessment (CGA) for health outcomes in older persons. Methods: Umbrella review of systematic reviews of the use of CGA in older adults searching in Pubmed, Embase, Scopus, Cochrane library and CINHAL until 05 November 2021. All possible health outcomes were eligible. Two independent reviewers extracted key data. The grading of evidence was carried out using the GRADE for intervention studies, whilst data regarding systematic reviews were reported as narrative findings. Results: Among 1, 683 papers, 31 systematic reviews (19 with meta-analysis) were considered, including 279, 744 subjects. Overall, 13/53 outcomes were statistically significant ( P < 0.05). There was high certainty of evidence that CGA reduces nursing home admission (risk ratio [RR] = 0.86; 95% confidence interval [CI]: 0.75–0.89), risk of falls (RR = 0.51; 95%CI: 0.29–0.89), and pressure sores (RR = 0.46; 95%CI: 0.24–0.89) in hospital medical setting; decreases the risk of delirium (OR = 0.71; 95%CI: 0.54–0.92) in hip fracture; decreases the risk of physical frailty in community-dwelling older adults (RR = 0.77; 95%CI: 0.64–0.93). Systematic reviews without meta-analysis indicate that CGA improves clinical outcomes in oncology, haematology, and in emergency department. Conclusions: CGA seems to be beneficial in the hospital medical setting for multiple health outcomes, with a high certainty of evidence. The evidence of benefits is less strong for the use of CGA in other settings.